2020
DOI: 10.1002/jclp.23077
|View full text |Cite
|
Sign up to set email alerts
|

Changes in clients and therapists experiences of therapeutic distance during psychodynamic therapy

Abstract: Attachment theory provides a framework for examining closeness–distance experiences in the development of the therapeutic relationship. Objective To examine changes in clients' and therapists' experiences of therapeutic distance along with psychodynamic therapy. Hypotheses: Clients' and therapists' comfort with closeness and distance will increase, and the client's autonomy and engagement will increase with time. Method A total of 67 clients and their 27 therapists underwent Relationship Paradigm interviews in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…Although not part of the research hypotheses, we found almost no reciprocal effects (improvement in a client's therapeutic distance relating to the therapist's alliance and vice versa). This connects to an earlier study that showed no dyadic influences in therapeutic distance scale changes of clients and therapists (Egozi et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although not part of the research hypotheses, we found almost no reciprocal effects (improvement in a client's therapeutic distance relating to the therapist's alliance and vice versa). This connects to an earlier study that showed no dyadic influences in therapeutic distance scale changes of clients and therapists (Egozi et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The TDS-O (Egozi et al, 2020(Egozi et al, , 2021 is based on the self-report measure developed by Mallinckrodt (TDS; Mallinckrodt et al, 2015).…”
Section: Therapeutic Distance Scale-observer Version (Tds-o)mentioning
confidence: 99%
“…The SRTD model predicts significant change in Growing Autonomy and Growing Engagement only for clients who manage to establish a secure attachment to their therapist. Nevertheless, the TDS-O proved to be a valuable assessment tool for the data analyzed in these two studies (Egozi et al, 2021a(Egozi et al, , 2021b. Further research is needed to evaluate the congruence of observer and client ratings of therapeutic distance.…”
Section: Corrective Emotional Experiencesmentioning
confidence: 99%
“…Taking a relational perspective that highlights the mutual aspects of the encounter between client and therapist (Aron, 1996;Muran, 2019;Safran & Muran, 2000; see also Chapter 5 by Tishby in this volume), we developed the Therapeutic Distance Scale Observer version (TDS-O; Egozi et al, 2020) to assess the therapeutic distance as experienced by each partner in the dyad. The TDS-O includes a version for the client and one for the therapist.…”
Section: Assessment Of Therapeutic Distancementioning
confidence: 99%
“…The TDS-O includes a version for the client and one for the therapist. Like the self-report TDS, the Observer versions also comprise four scales: Too Distant (the partner is perceived as distant and inaccessible), Too Close (the partner is perceived as intrusive and forcing closeness), Growing Autonomy (therapy encourages clients to make independent decisions and to take the initiative, from either the client's or the therapist's view), and Growing Engagement (clients' ability to discuss sensitive issues and relinquish concerns regarding the need to reveal themselves, from either the client's or the therapist's view; Egozi et al, 2020).…”
Section: Assessment Of Therapeutic Distancementioning
confidence: 99%